Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/pcmr.12234
|View full text |Cite
|
Sign up to set email alerts
|

Factors secreted by irradiated aged fibroblasts induce solar lentigo in pigmented reconstructed epidermis

Abstract: Subscribe to PCMR and stay up-to-date with the only journal committed to publishing basic research in melanoma and pigment cell biology As a member of the IFPCS or the SMR you automatically get online access to PCMR. Sign up as a member today at www.ifpcs.org or at www.societymelanomaresarch.orgIf you wish to order reprints of this article, please see the guidelines here Submit your next paper to PCMR online at http://mc.manuscriptcentral.com/pcmr

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 10 publications
(12 reference statements)
2
46
0
Order By: Relevance
“…Certain inflammatory factors such as leukotriene C4 also induce chronic growth stimulation of human adult melanocytes (Medrano et al, 1993). On the other hand, it has been shown that different fibroblast-secreted melanogenic peptides could modulate melanocyte numbers in monolayer cultures (Cario-André et al, 2006;Salducci et al, 2014). In vitro results on monolayers and skin reconstructs, using growth factors and conditioned medium suggested that murine fibroblasts secrete soluble factors that can stimulate normal human melanocytes.…”
Section: Discussionmentioning
confidence: 97%
“…Certain inflammatory factors such as leukotriene C4 also induce chronic growth stimulation of human adult melanocytes (Medrano et al, 1993). On the other hand, it has been shown that different fibroblast-secreted melanogenic peptides could modulate melanocyte numbers in monolayer cultures (Cario-André et al, 2006;Salducci et al, 2014). In vitro results on monolayers and skin reconstructs, using growth factors and conditioned medium suggested that murine fibroblasts secrete soluble factors that can stimulate normal human melanocytes.…”
Section: Discussionmentioning
confidence: 97%
“…Other features such as damage to the basal membrane, an increase in blood vessels and in dermal mast cells and lymphohistiocytic infiltration have been described . The aetiology of melasma seems more complex than that of senile lentigo, another photoageing disorder, which can be attributed mainly to dysregulation of UVA‐induced fibroblasts . As summarized by Passeron and Picardo, solar radiation (UVA, UVB and visible light) can induce melanogenesis in melasma by stimulating melanocytes directly or indirectly via secretion of melanogenic factors by keratinocytes, fibroblasts, endothelial cells and probably sebocytes.…”
Section: Hormones and Melasma In Vivomentioning
confidence: 99%
“…First, in melasma, the number of blood vessels and mast cells is greater in lesional skin than in perilesional skin . Second, dermal regulation of pigmentation has already been demonstrated in vitro, [ ] in vivo and in pigmentary disorders such as senile lentigo and vitiligo and has been hypothesized in melasma . Furthermore, in systemic scleroderma (SSc) whose main skin feature is fibrosis, characteristic modifications of the fibroblast functional phenotype are thought to be due to an interplay between damaged endothelial cells, immune cells and their soluble mediators .…”
Section: Effects Of Sex Steroid Hormones On Dermal Compartment and Inmentioning
confidence: 99%
“…Ultraviolet‐induced skin pigmentation is regulated by interactions between melanocytes and neighboring cells, such as keratinocytes or fibroblasts . Specifically, an important role of photoaged fibroblasts in the development of UV‐associated hyperpigmentary disorders, solar lentigo or melasma has been suggested . In addition to fibroblasts, growing evidence also implicates blood vessels in pigmentation .…”
Section: Introductionmentioning
confidence: 99%